Optimizing the STB/BBNJ arrangements: based on comparing three STB operational modalities - Li, You; Jiang, Xiaoyi (Frontiers in Marine Science, 2025)
A Scientific and Technical Body (STB) is to be established under the BBNJ Agreement to provide high-quality assessments to support policy decisions. However, its terms of reference and modalities yet to be determined. Based on the three effectiveness factors of saliency, credibility and legitimacy, we classify the existing STB operational modalities into evaluation-oriented modality, recommendation-oriented modality, and decision-oriented modality. After comparing the three STB operational modalities, we conclude that the STB/BBNJ should be designed mainly based on a decision-oriented modality. Under this modality, the STB/BBNJ terms of reference may follow the principles of maintaining STB independence and preventing excessive powers. In accordance with the principles and to realise the conservation and sustainable use of marine biodiversity, we suggest that the STB/BBNJ institutional arrangements should consider to include (1) a multidisciplinary expert involvement mechanism; (2) a transparent oversight mechanism; (3) dynamic adjustment mechanism; and (4) cooperation and coordination mechanism.